Sex Differences in Categorical Adaptation for Faces and Chinese Characters during Early Perceptual Processing - Zhu, Cuiyin; Ma, Xiaoli; Ji, Lihong; Chen, Shuang; Cao, Xiaohua (Frontiers in Human Neuroscience, 2018)
Previous event-related potential studies support sex differences in the N170 response during face and word processing; however, it remains unclear whether N170 categorical adaptation for faces and words is different between women and men. Using an adaptation paradigm, in which an adaptor and subsequent test stimulus are presented during each trial, the present study investigated N170 categorical adaptation for faces and Chinese characters in both women and men. The results demonstrated that the N170 amplitude elicited by test stimuli in within-category condition was lower than in control category condition, and this was observed during both face and Chinese character processing in women and men. In addition, we found that men have greater N170 categorical adaptation for face and word processing than women. There was also a significant correlation between N170 categorical adaptation indices for face and Chinese character processing in men, which did not occur in women. These findings suggest that men and women process repeated faces or words differently.